THE EFFECTIVENESS OF USING PAIR CHECK MODEL TO TEACH READING AT THE EIGHTH GRADE STUDENTS OF SMP N 02 BUAY MADANG - Muhammad Muklas (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2016)
The objective of this Research entitled â€œThe effectiveness of using pair check model to teach reading at the eighth grade student of SMP N 02 Buay Madangâ€. The formulation of this research was there any significant difference between the students who are taught by using pair check model and the students who are taught by using conventional model to teach reading at the eighth grade students of SMP N 02 Buay Madang. The objective of this research was to measure whether or not there was any significant difference between students who are taught teaching reading through pair check model and who are taught through conventional model at the eighth grade students of SMP N 02 Buay Madang. In this research experimental method and true experimental design was used. It was involved two classes they are; experimental class and control class. The population of the research was 88 students of the eighth grade of SMP N 02 Buay Madang, and the sample of the research was 59 that taken through cluster random sampling that divided into two class they are 30 as experimental class and 29 as control class. Meanwhile, for collecting the data used reading test. After that, the data were analyzed by using independent t-test formula. And based on the results of findings, it was found that the mean of post- test score in experimental class was 68.66 and the mean of post- test in control class was 64.65. Beside that, the t-obtained was 0.000 and the t-table with df 57 (59-2) with 95% or 0.05 significant level was 2.0025. Therefore, the research concluded that the alternative hypothesis (Ha) was accepted because the t- obtained was lowers than the t- table ( 0.000 < 2.0025). It also meant that there was any significant difference between students who are taught through Pair Check Model and who are taught through Conventional Model.